Hedge Funds and Stock Market Efficiency - Kokkonen, Joni; Suominen, Matti (Management Science, 2015)
We measure misvaluation using the discounted residual income model. As shown in the literature, this measure of stocks' misvaluation significantly explains their future cross-sectional returns. We measure the market-level misvaluation (market inefficiency) by the misvaluation spread: the difference in the misvaluation of the most overvalued and undervalued shares. We show that the misvaluation spread is a strong predictor of a misvaluation-based long–short portfolio’s returns, reinforcing the hypothesis that it proxies for the level of mispricing in the stock market. Using data on hedge fund returns, hedge fund industry assets under management, flows, and individual hedge fund holdings, we present evidence that hedge funds' trading reduces market-level misvaluation. Our results are robust across different time periods and are not driven by market liquidity. Moreover, we find that mutual funds do not have the price-correcting effect that hedge funds have. This paper was accepted by Wei Jiang, finance.